2006
DOI: 10.1111/j.1474-9726.2006.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrones as therapeutics in age‐related diseases

Abstract: SummaryAge-related diseases deprive individuals of a higher quality of life and therefore therapeutics for their treatment provide significant potential. An overview of the observations of nitrones as potential therapeutics in several age-related diseases is presented. Treatment of acute ischemic stroke is one condition where a nitrone (NXY-059) is in late phase 3 clinical trials now. Also presented is a summary of the most recent work we have accomplished on the anticancer activity of the nitrones in a hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 51 publications
1
55
0
1
Order By: Relevance
“…Although the exact therapeutic mechanism of nitrones such as STAZN is not known, reduction of levels of reactive oxygen species [27] and the production of nitric oxide [28] are two possibilities. Interestingly, these two mechanisms have also been proposed for postconditioning -the phenomenon in which rapid intermittent interruptions of blood flow applied at the onset of reperfusion result in cardioprotection, as demonstrated both in animal models and humans [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact therapeutic mechanism of nitrones such as STAZN is not known, reduction of levels of reactive oxygen species [27] and the production of nitric oxide [28] are two possibilities. Interestingly, these two mechanisms have also been proposed for postconditioning -the phenomenon in which rapid intermittent interruptions of blood flow applied at the onset of reperfusion result in cardioprotection, as demonstrated both in animal models and humans [29].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological and nutritional approaches to retard aging and increase longevity have been proposed (Floyd, 2006, Joseph et al, 2005. Large-scale screens are being considered for a number of model organisms to accelerate discovery of compounds with the greatest potential for extending lifespan (Bauer et al, 2004, Wang et al, 2004.…”
Section: Discussionmentioning
confidence: 99%
“…γ-, but not α-, tocopherol slightly extended lifespan in nematodes, but neither significantly affected lifespan in two fly species. This study shows that a comparative approach, utilizing multiple invertebrate species, can increase the robustness of invertebrate-based pilot screens for prolongevity interventions.Pharmacological and nutritional approaches to retard aging and increase longevity have been proposed (Floyd, 2006, Joseph et al, 2005. Large-scale screens are being considered for a number of model organisms to accelerate discovery of compounds with the greatest potential for extending lifespan (Bauer et al, 2004, Wang et al, 2004.…”
mentioning
confidence: 99%
“…We showed that administering PBN as well as the 3-hydroxy and 4-hydroxyl derivatives in the diet caused selective enhanced killing of the cells within the preneoplastic lesions at 16 weeks but had no effect of the cells in the surrounding liver tissue 84,85 . We later surmised that the enhanced selective killing of the cells within the preneoplastic lesion by PBN and active derivatives was due to their suppression of NO formation therefore allowing the normal cellular stressors to enhance their apoptosis 88 .…”
Section: And 2)mentioning
confidence: 99%